Introduction. (22nd June 2022) - Rauhut, Michael; Peter, Beate
Abstract : The history of popular music in the German Democratic Republic (GDR) is marked by disproportion on the one hand and gaps on the other. The majority of studies focus on phenomena that are assigned subversive qualities and the potential to lead to fundamental social change: jazz, blues, folk, and various styles of rock music. These genres are well documented in the archives that have opened up since the fall of the Berlin Wall. As Schlager, musicals or the operetta are considered to be light entertainment rather than culture, they are rarely researched. Gaps also exist with regard to the analysis of the musical artefact itself. Most research projects are dominated by an interest in historical events and focus on political forces and social effects, and the music itself is often ignored in favour of a discussion of the socio-political framework. This special issue presents new findings and invites a discussion on those methods that may contribute to a broadening of the perspectives on the history of popular music in the GDR.